1994
DOI: 10.1111/j.1600-0609.1994.tb01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human erythropoietin on platelets in patients with anemia of renal failure: correlation of platelet count with erythropoietic activity and iron parameters

Abstract: We examined the effect of treatment with rHuEpo on platelet counts in 61 hemodialysis patients and correlated them with changes in erythropoietic activity, iron status and inflammation. Platelets (109/l) increased from 220 ±80 to 245 ±102 after 14 days and stabilized at that level up to day 90 (p<0.0001). The increment was similar in complete or partial responders but was not observed in failures. Serum transferrin receptor (sTfR, a measure of total erythropoiesis) and Hct rose much more progressively, but rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Adapted from Regidor et al 13 In addition to associations of blood hemoglobin with mortality and hospitalizations in the CKD population, anemia is associated with fatigue, weakness, shortness of breath, and a decreased health-related quality of life. 33,34 Furthermore, hemoglobin overshoot may be associated with various safety concerns, including the development of elevated BP with risk for hypertensive encephalopathy, 35 iron deficiency, 36 high platelet count, [37][38][39] thrombotic events, 40 and accelerated left ventricular dysfunction and hypertrophy. 7 …”
Section: Consequences Of Hemoglobin Variabilitymentioning
confidence: 99%
“…Adapted from Regidor et al 13 In addition to associations of blood hemoglobin with mortality and hospitalizations in the CKD population, anemia is associated with fatigue, weakness, shortness of breath, and a decreased health-related quality of life. 33,34 Furthermore, hemoglobin overshoot may be associated with various safety concerns, including the development of elevated BP with risk for hypertensive encephalopathy, 35 iron deficiency, 36 high platelet count, [37][38][39] thrombotic events, 40 and accelerated left ventricular dysfunction and hypertrophy. 7 …”
Section: Consequences Of Hemoglobin Variabilitymentioning
confidence: 99%
“…(18) Therefore, we often adjust the ESA dosage according to the mean hemoglobin level and ignore real hemoglobin cycling and hemoglobin excursions. (9) Hemoglobin overshooting may be associated with various complications, including hypertension, (19) high platelet counts, (20) and thrombotic events. (21) Our study showed a significantly reduced ESA dosage in patients who maintained low amplitude in conjunction with high hemoglobin levels (LAH group), while patients exhibiting high amplitude in conjunction with average hemoglobin levels within the target range (HA group) had ESA usage similar to that of other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Eschbach et al [47] found that treatment with epoetin alfa to maintain a hematocrit of 35% in hemodialysis patients resulted in an increase in mean platelet counts. Similarly, Beguin et al [48] also found a significant increase in platelet count in hemodialysis patients treated with epoetin. Earlier observations in animal studies with especially high doses of ESAs (like in some RCTs) pointed to a significant increase in platelet count as well [49,50] .…”
Section: How Could We Reduce Cardiovascular Events and Cardiac Mortalmentioning
confidence: 91%